The Political Role of the United Arab Emirates in The Parliament of The Arab League - Awad, Haider Saleh; Mal Allah, Izdihar Muayad (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: This study examines the establishment of the Transitional Arab Parliament within the reform of the Arab joint action system between 2005 and 2011. Specific Background: The Parliament emerged from Arab reform initiatives since 2003 aimed at expanding popular participation and introducing oversight mechanisms within the League of Arab States. Knowledge Gap: Limited scholarly focus exists on the institutional performance and political roles of member states, particularly the United Arab Emirates, within this transitional parliamentary framework. Aims: The study aims to analyze the legal foundation, organizational structure, consultative competencies, and operational mechanisms of the Parliament, while assessing its performance and the role of the United Arab Emirates. Results: Findings indicate that the Parliament functioned as a consultative body addressing major regional issues, including the Palestinian cause, Sudan, and Arab–Iranian dialogue, while also reflecting institutional limitations during its transitional phase. Novelty: The study provides a focused examination of the United Arab Emirates’ political role within the Parliament alongside institutional analysis of the Arab parliamentary experiment. Implications: The findings contribute to understanding regional parliamentary development and highlight structural challenges in advancing collective Arab institutional frameworks. Highlights:• Transitional parliamentary body addressed key regional political issues• Institutional structure combined consultative and oversight functions• Member state participation revealed structural and procedural limitations Keywords: Arab Parliament, United Arab Emirates, League Of Arab States, Institutional Reform, Regional Governance